Introducing Indonesian endemism, its threat and conservation solution for SMA Negeri 10 students in Kamarian Village, West Seram Regency, Maluku - Leimena, Handy Erwin Pier; Seumahu, Cecilia Anna; Sahertian, Dece Elizabeth; Ukratalo, Abdul Mahid; Kaihena, Martha (Pascasarjana Universitas Mataram, 2024)
West Seram Regency on Seram Island in Maluku Province, Indonesia has extraordinary biodiversity and is the habitat of several endemic species of Maluku and Indonesia. As a form of implementation of the dharma of community service, socialization was conducted with students of SMA Negeri 10 in Kamarian Village, West Seram Regency, Maluku about Indonesian endemism, its threats and conservation. The socialization was attended by 38 students. The socialization results indicate that 91% of students demonstrated a good understanding of endemic species, and 82% of students obtained information on endemic species from this activity. Additionally, students were able to identify 11 Indonesian endemic species, as well as the threats and efforts to protect them. This activity has the potential to increase environmental awareness among school students, the nation's young generation.